2019
DOI: 10.1103/physrevb.99.195423
|View full text |Cite
|
Sign up to set email alerts
|

Topological surface states in thick partially relaxed HgTe films

Abstract: Surface states of topological insulators (TIs) have been playing the central role in the majority of outstanding investigations in low-dimensional electron systems for more than 10 years. TIs based on high quality strained HgTe films demonstrate a variety of subtle physical effects. The strain leads to a bulk band gap, but limits a maximum HgTe strained film thickness, and, therefore, the majority of experiments were performed on the films with a thickness of less than 100 nm. Since a spatial separation of top… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 41 publications
3
19
1
Order By: Relevance
“…1 (a) we schematically show cross-section and a schematic top view of the system under study. The 200-nm HgTe film is sandwiched between thin Cd 0.6 Hg 0.4 Te barriers and is partially relaxed [25], a Ti/Au gate has been deposited on the 200-nm Si 3 N 4 plus 100-nm SiO 2 insulator grown by a low temperature chemical vapor deposition process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 (a) we schematically show cross-section and a schematic top view of the system under study. The 200-nm HgTe film is sandwiched between thin Cd 0.6 Hg 0.4 Te barriers and is partially relaxed [25], a Ti/Au gate has been deposited on the 200-nm Si 3 N 4 plus 100-nm SiO 2 insulator grown by a low temperature chemical vapor deposition process.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the study of thicker HgTe films is also desirable because of a higher separation between the surface states, their weaker mutual electrostatic coupling, and possible hybridization. Recently [25,5], it has been shown that partially relaxed 200-nm HgTe films have a near zero bulk energy gap, but also host similar to what the strained 80-nm system has -the spin non-degenerate surface states.…”
Section: Introductionmentioning
confidence: 99%
“…This case corresponds to the ideal reflection of electrons on the impurity. Fourier spectrum of conductance oscillations is convenient representation for the analysis of experimental data [37,38]. Remarkably, that Fourier coefficients of the transmissions coefficient, T (n) = dφ T (φ)e i4πφn , obey universal relation…”
Section: Calculation Of Conductance and Polarizationmentioning
confidence: 99%
“…The values of sheet densities and mobilities for different types of carriers can be extracted using the two‐component classical Drude model, which was successfully implemented for thin HgTe films. [ 11,38,41 ] The values of sheet electron density nnormals obtained from such modeling are shown in Table 1. In this table, we also provide the values of average volume electron density n , which are obtained from the corresponding sheet electron densities nnormals as n=nsfalse/w, where w denotes the corresponding CdxHg1xTe film thicknesses (Figure 1b–f).…”
Section: Samplesmentioning
confidence: 99%